HUBUNGAN KARAKTERISTIK DAN TINGKAT PENGETAHUAN DENGAN PERILAKU PENCEGAHAN COVID-19PADA MASYARAKAT DESA PAYA BUJOK BLANG PASE KOTA LANGSA - Khairunnisa z Khairunnisa z; Rizka Sofia; Sulfia Magfirah (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2021)
Covid-19 is a global outbreak that is not ended yet and a significant amount of positive cases are keep increasing. Positive cases and the death rates are increasing in Indonesia, therefore it is necessary to break the chain to prevent the spread of Covid-19. The purpose of this research is to find out the relation between characteristics and knowledge levels with prevention behavior of Covid-19 in society of Paya Bujok Blang Pase Langsa City. The research method that has been used was an analytical study with cross sectional design and the statistical analysis was the chi square test. The sampling technique in this research used a simple random sampling with a total of 260 people according to inclusion and exclusion criteria. The results of the univariate analysis found that the highest level of knowledge was good (73.5%), and the highest level of behavior was good (67.7%). The results of the bivariate analysis found that there was no relationship between gender and Covid-19 prevention behavior (p value 0.427), there was no relationship between work and Covid-19 prevention behavior (p value 0.230), and there was a relationship between age, education, and knowledge with Covid-19 prevention behavior (p value 0.000). The conclusion of this research is there is no relationship between gender and work with Covid-19 prevention behavior and there is a relationship between age, education, and level of knowledge with Covid-19 prevention behavior.